Development of an Ecoenzyme and Liquid Organic Fertilizer-Based Biobattery KIT to Support Electrochemistry Learning in Junior High School - Muhammad Yusron Nadhif; Dody Rahayu Prasetyo (Jurnal Pendidikan Kimia Indonesia, 2025)
This study aimed to develop and evaluate an interactive learning medium in the form of a Biobattery KIT based on ecoenzyme and liquid organic fertilizer (LOF) to support electrochemistry learning at the junior high school level. The learning media introduce concepts of electrolyte solutions, redox reactions, and simple voltaic cells through environmentally friendly organic materials. This study is a Research and Development (R&D) study using the 4D development model (define, design, develop, and disseminate). The developed product was validated by material and media experts and tested on students to evaluate feasibility and learning potential. The validation results indicated high feasibility, with material expert validation reaching 97.5% and media expert validation reaching 100%. Student trials showed positive responses with an effectiveness score of 90%, indicating that the Biobattery KIT has strong potential to facilitate students’ conceptual understanding of electrochemical principles and renewable energy concepts. The findings suggest that the ecoenzyme and LOF-based Biobattery KIT can serve as an innovative and sustainable learning medium for electrochemistry education at the junior high school level.